STRATEGI PENGEMBANGAN DAN PENEMPATAN PRODUK SUPLEMEN MAKANAN DARI BAHAN NABATI - Mohamad Harisudin (Universitas Sebelas Maret, 2005)
Research aim to identification the concept of food supplement product from herbs as according to request of consumer of high school student segment, producing of it and spesify its product position strategy